A comparison of the effects of contemporary dressings and 1% Povidone Iodine on the healing of diabetic ulceration: A Quasy Experiment - Indra Ariani; Dimas Putra Harsya; Asmat Burhan (Journal of Wound Research and Technology, 2024)
Background: Diabetes ulcers are a consequence of diabetes mellitus (DM). Modern dressing techniques are essential for the treatment of diabetic ulcers, which are lesions that necessitate specific attention and control. The researchers set out to find out how a diabetic ulcer wound healing score changed after using a contemporary dressing. Aims: Analyse the effectiveness of dressing and povidone iodine 1% on diabetic foot ulcer healing. Design and Methods: Quasi experiment, pre-test and post-test of experiment group using modern dressing and control group using iodine. Total sampling technique was used in this study with a total of 84 patients. Data analysis was performed with a parametric test, namely paired t-test, and independent t-test. Results: Both groups originally exhibited comparable wound diameters. On the 30th day, there was a decrease in wound size score (MD-CI) due to modern dressing. The drop was -1.94 with a 95% confidence interval of -4.37 to 0.14. The p-value was 0.043 and the r-squared value was -0.121. On the 60th day, the MD-CI treatment resulted in a reduction in wound size of -5.14 (95% confidence interval: -11.50 to -1.34; p=0.013; r2= -0.416). Conclusion: At first, contemporary dressing therapy achieved a marginal reduction in lesion size. However, lesion size decreased substantially in diabetic foot ulcers after day 60. It is possible to suggest this intervention as a therapeutic approach for diabetic foot ulcers